A forgotten approach after cardiac arrest due to acute myocardial ınfarction: Neuroprotective therapeutic hypothermia - Özçelik, Abdullah; Alsancak, Yakup; Gürbüz, Ahmet Seyfeddin; İçli, Abdullah and Soylu, Ahmet (Journal of Surgery and Medicine, 2018)
In patients with spontaneous circulation after cardiopulmonary resuscitation, therapeutic hypothermia is defined as the reduction of body temperature to 32-34 ° C within the first 4-6 hours for neuroprotective purposes and to be maintained at this level for 12-24 hours after reaching the target temperature. Therapeutic hypothermia has been practiced since the 1940s. The aim of therapeutic hypothermia is to reduce cerebral edema, convulsive activity, metabolic demand and associated complications by providing low body heat. Therapeutic hypothermia is applied to increase life expectancy and quality of life. In out-of-hospital cardiac arrest, should be performed in comatose patients where initial rhythm is ventricular fibrillation and spontaneous circulation is returned. Herein, we present a 44 years old patient who had an aborted sudden cardiac death due to acute myocardial infarction and performing cardiopulmonary resuscitation for 30 minutes and discharged after 6 days with a successful therapeutic hypothermia.